The role of UNHCR in the settlement of Iraqi displaced persons, 2003-2010 - Maktouf, Muthana Nemeh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The US led invasion and toppling of the Ba'ath Party and Saddam Hussein's regime in 2003 created a massive refugee flow of more than two million Iraqis who fled the country. This flow has been described as the second largest exodus in the Middle East since the Palestinian displacement in 1948. This study examines the root causes of this displacement and the status of Iraqi refugees in the host countries that absorbed them, namely Syria, Jordan, Iran, Turkey, and Lebanon. Such a large flow of refugees has required UNHCR to implement its mandate by adopting different activities to encourage these countries to recognise Iraqis as refugees rather than ―guests‖ and protect them from non-refoulement. This study adopts a conceptual framework that is approached qualitatively by referring to official documents, reports, books, and journals as sources of data. It examines the UNHCR activities, mainly temporary sheltering and support with basic needs such as food, health and education, voluntary repatriation and reintegration, and third country resettlement. These activities have been studied in detail in relation to each host country respectively. The study found that UNHCR achieved both success and failure in implementing its activities. It is handicapped in implementing its operations effectively for different reasons. Firstly, UNHCR has little autonomy and a limited mandate; both influenced by donor states which determine resettlement activities, making UNHCR partially successful in regards to third country resettlement. Secondly, UNHCR cannot implement voluntary return and reintegration because the root causes of the displacement continue to exist within Iraq. Thirdly, the provision of basic needs in terms of food, health care and education has been partially successful in meeting the needs of refugees.